Systematic Literature Review: Peningkatan Hasil Belajar IPS Menggunakan Media Visual pada Siswa Sekolah Dasar - Aisyah Fadilla Ginting; Novita Girsang; Siti Salwa Arianto; Fadjarlin Hulu; Ledi Anna Siregar (Journal on Education, 2025)
This study aims to evaluate the effectiveness of using visual media in improving student learning outcomes in social studies. The method used in this study is a Systematic Literature Review (SLR) by analyzing various relevant and credible literature sources. The results of the study indicate that visual media play an important role in improving students' understanding and interest in learning. The integration of visual elements with the delivery of Social Studies material has proven to help students understand concepts more concretely, capture their attention, and create a more interactive learning experience. Thus, the use of visual media can serve as an effective alternative learning strategy to enhance learning outcomes in Social Studies.